Factors associated with conjugal violence in the emergency center woman - Límaco Ninahuanca, Wilman Josue (2019)
The purpose of the present investigation was to identify and analyse the factors associated with violence against women in Peru, using logistic regression model. A quantitative, non-experimental, transversal and explanatory approach was used, based on the Demographic and Family Health Survey of the year 2013 of the National Institute of Statistics and Informatics, and whose probabilistic sample in-cluded 22 920 women of childbearing age from 15 to 49 years. The results obtained at the descriptive level showed that violence against women in Peru occurs mainly through psychological - verbal violence (67,5 %), which represented almost twice the physical violence (35,7 %) and more than eight times sexual violence (8,4 %). Al-so, a logistic regression model was built, and although they presented limitations in the speciﬁcity and sensitivity, i was veriﬁed that variables such as husband’s al-cohol consumption, that she currently works and problem if I am pregnant , were homogeneous and concurrent factors in the three models developed for psychological violence- verbal, physical and sexual.